Using Coding Apps to Support Literacy Instruction and Develop Coding Literacy. - Hutchison, Amy; Nadolny, Larysa; Estapa, Anne (Reading Teacher, 2016)
In this article the authors present the concept of Coding Literacy and describe the ways in which coding apps can support the development of Coding Literacy and disciplinary and digital literacy skills. Through detailed examples, we describe how coding apps can be integrated into literacy instruction to support learning of the Common Core English Language Arts standards. The authors also provide suggestions for getting started with coding apps and discuss aspects of instruction for teachers to consider as they plan to integrate coding apps into their classrooms.